Investigation of situational interest effects on learning using physiological sensors: Preliminary result - Babiker, A. (Institute of Electrical and Electronics Engineers Inc., 2017)
Recently, extensive attention is given to researches that develop educational outcome by raising student's interest. There are two types of interest, one of them is situational interest that depends on the situation and time. It has been identified as a vital motivational element in developing students' academic performances. The purpose of this research is to present a novel approach to detect the distinct patterns of situational interest while resembling classroom environment using physiological sensors, particularly EEG signals. Personal Interest (PI) test, Study Interest (SI) test and knowledge tests are used to evaluate subjectively student's interest. Objective data obtained using Emotive EPOC supports subjective result and shows that brain activities in frontal and left hemisphere can be associated with situational interest during learning process. © 2016 IEEE.